Theplace of blacks in the construction of national identity - Vanderley, Selma de Fatima; Barbosa, Maria Valeria [UNESP] (Univ Federal Espirito Santo, 2023)
This paper aims to revisit the post-abolition period in order to describe the place of blacks with the establishment of the Republic and the challenge posed by the new developments in the national context regarding the role of blacks in the construction of national identity.It goes through the conceptions of racial theories, immigration policy and approaches how the inculcation and assimilation of the whitening ideals that marked the beginning of the twentieth century took place.
Keywords: racial theories; immigration; whitening; assimilation